MANGANESE(III)-BASED REACTION OF l,l-DIARYLETHENES WITH ALKYL 2-0XOCYCLOPENTANECARBOXYLATES: AN EFFICIENT ROUTE TO 2-0XABICYCLO[3.3.0]OCTANE DERIVATIVES - Huỳnh Thái Kim Ngân; Nguyễn Văn Hạ (Tạp chí Khoa học Đại học Đà Lạt)
1,1-Diarylethenes react with alkyl 2-oxocyclopentanecarbo-xylates in the presence of manganese triacetate leading to the formation of 1-acetoxy-3,3-diaryl-5-ethoxycarbonyl-2-oxabicyclo[3.3.O]octane or 2-(2,2-diarylethenyl)-2-ethoxycarbonylcyclopentanone in good yields. Substituents on aryl ring of the alkenes have remarkable influence on the product type. The reaction mechanism is discussed.